Prevalence of fascioliasis (liver flukes) infection in cattle and buffaloes slaughtered at the municipal abattoir of El-Kharga, Egypt - Nagwa T. Elshraway; Wafaa G. Mahmoud (Veterinary World, 2017)
Aim: The main objectives of this study were to determine the prevalence of fascioliasis infections in cattle and buffaloes, slaughtered in El-Kharga city slaughterhouse at New Valley Governorate.